Packet-based routing algorithm in DTN based on the intimacy between nodes - En WANG; Yong-jian YANG; Wei-dan ZHAO; Lin-lu LIU (Tongxin xuebao)
Through analyzing the moving law of nodes,the topology is defined based on intimacy between nodes by using the thoughts of reducing redundant copies through clustering in MANET and mining social community in social network for reference.Take topological trim according to the weight of edges and dig out groups of nodes which have higher inti-macy degree.And also improve the spray and wait routing protocol according to the group of source and destination nodes.Then put forward a packet-based routing algorithm in DTN based on the intimacy between nodes.Simulation result shows that this routing algorithm could effectively increase the delivery ratio and reduce delay.